Transformasi LPP TVRI di Tengah Pergolakan Politik dan Struktural - Retno Intani (Program Studi Ilmu Komunikasi, 2013)
TVRI still faces an identity crisis between representing the public interest with the interests of power. The influence of power remains strong even though TVRI has been established as public service broadcasting since 2002. This article tries to analyze the political and structural issues that interfere the transformation of TVRI as public service broadcasting. Various conflicts of interest, especially from the government and parliament eventually obstruct TVRI to act as a public broadcaster in the real sense.